(untitled) (Jurnal Manajemen Bisnis, 2024)
This study explores the impact of job satisfaction as a mediator on the performance of Generation Z employees. The research focuses on examining the relationship between work motivation, leadership style, work competence, job satisfaction, and employee performance. Using a quantitative methodology, data were collected through surveys and analyzed using statistical tools such as SPSS and SmartPLS. The results indicate that job satisfaction significantly mediates the relationship between the independent variables (work motivation, leadership style, and work competence) and employee performance. These findings have important implications for organizational strategies aimed at improving employee performance through enhanced job satisfaction.